Interaction processes in Latin American Instagramers. The case of Peru and Colombia during 2019 - Gonzalez-Carrion, Erika-Lucia (2020)
In order to evaluate the forms of interaction in the main Instagramers from Peru and Colombia, an exploratory analysis of their profiles was carried out on the Instagram audiovisual platform during 2019. For this reason, firstly, the Heepsy tool was used to establish the influencers with greater impact within the platform in both countries and then, through the monitoring tools Fan Page Karma and Social Blade, to determine a set of variables and parameters regarding their interaction. The results show that the audience index is higher for Instagramers from Colombia than for the ones from Peru. In addition, there is a clear trend among digital audiences to value content through likes as a sign of interaction with it, but on the other hand, there is a representative decrease in expressing their impressions with words and comments regarding what they observe; this is also established by the low levels of commitment registered by most Instagramers.